Geoinformation technologies as a tool for developing geospatial thinking skills (Journal of Educational Sciences, 2024)
The use of geospatial technologies is becoming increasingly important in geography education, enabling activities such as spatial data retrieval, sampling, organised storage and transfer of necessary information. However, this process is very slow due to many obstacles that hinder the implementation of geospatial technologies in secondary education. Therefore, the purpose of this study was to analyse the current status of geospatial technologies in teaching geography in schools in Kazakhstan and to assess the potential of these technologies to develop students' geospatial skills. The state of application of geospatial technologies in secondary education in Kazakhstan was determined by a survey. The survey involved 208 geography teachers from 17 regions and 3 large cities of Kazakhstan. The survey results showed that 96.2% of respondents use geospatial technologies (geographic information systems - GIS, software, mapping services, geoportals, mobile GIS applications). The most common are mobile GIS applications (69.5%) and mapping services (21.4%). It was also found that 24.1% of respondents use ArcGis and 20.7% use QGIS for GIS-based data design. Although the content of typical secondary school programmes and textbooks reflects the problem of practical application of GIS technologies, it was found that teachers face a number of obstacles in using them. Therefore, teachers would benefit from using not only GIS but also geospatial technologies in general when teaching school geography. In the future, geospatial technologies will help students to develop geospatial thinking skills due to their multifunctional capabilities.Key words: school geography, geographic information technology, development of geospatial thinking.